The anti-vaccine movements on Facebook and fake news in the COVID-19 pandemic in Brazil - Marcelle Medeiros Teixeira; Dilton Ribeiro Couto Junior; Velloso, Luciana (Journal of Learning Styles, 2024)
The text, part of the results of a recently concluded master’s research, analyzes the dissemination of fake news focused in questioning the reliability of scientific studies in times of the COVID-19 pandemic in Brazil. This distrust from the population feeds a favorable scenario for the strengthening of online anti-vaccine movements in a period of human history marked by the loss of many lives to the disease. We are concerned about the threat of this movement, as we understand that the vaccine cannot be understood only as an individual protection, but as a social protection. We adopted the cartographic method to support, theoretically and methodologically, the fieldwork on Facebook, aimed at analyzing posts made between 2020 and 2021 and that show different arguments triggered by people who are part of the anti-vaccine movements. The research recognizes the need for an education that aims to expand the debate about the dangers of misinformation in the middle of a pandemic.
Keywords: Pandemic; fake news; anti-vaccination movements; scientific denials; education